Aerodynamic Characteristics Improving of S809 Airfoil in Wind Turbine with Microtab - Ressan Faris Al-Maliky (Engineering and Technology Journal, 2012)
In present work numerical two dimensions, steady, incompressible, turbulent flow past S809 wind turbine airfoil with microtab at 95% of chord length of leading edge in lower surface is analyzed by Fluent (6.2) program for model consists of S809 airfoil without and with microtab at 95% of chord line have height 1.1% and other 2% of chord length undergo to turbulent flow k-. model, the flow has Reynolds number is 106. The results are represented by velocity contour and vector. Aerodynamic coefficients are drawn in graph. The results are showed an increase lift and drag coefficient in existence microtab locate 95% of chord at it's height 1.1% and 2% of chord to range of attack angle (0, 5, 10, 15, 20) degrees. The results compare with experimental data of standard airfoil and existence 1.1% chord length microtab and it is approximately good. Values of lift & drag coefficient are increased for the existence of 1.1% chord length microtab while in case the existence of microtab 2% chord length lift coefficient increased which it's max. increment by 46% while, drag coefficient decreased it's min. increment to be 26% but not full range of attack angle.